Bechterew's Phenomenon in Bilateral Sequential Vestibular Neuritis: A Report of Two Cases - Kim, Yehree; Jin, Siyeon; Kim, Ji-Soo; Koo, Ja-Won (Frontiers in Neurology, 2022)
The brain can compensate vestibular imbalance. When unilateral labyrinthine function is lost, the asymmetry between the peripheral vestibular inputs is compensated centrally by readjusting the signal difference from both ears and regaining vestibular balance. If the other healthy labyrinth is destroyed, the vestibular nuclei again become imbalanced, creating a spontaneous nystagmus even though there is no input to the vestibular nuclei from either labyrinth. This is called Bechterew’s phenomenon; a rare and not widely recognized phenomenon which occurs in cases of bilateral sequential vestibular neuritis. This is of clinical importance because spontaneous nystagmus with bilaterally absent or diminished caloric responses may give a misleading impression of a central lesion rather than a second peripheral lesion superimposed upon the effects of central compensation for the first. Though well documented in experimental animals, this phenomenon rarely occurs in human beings. The objective of this study is to highlight the characteristics and the progression of test results from two patients from our own experience. Along with careful history taking and physical examination, a complex interpretation of various vestibular function tests, including induced nystagmus, head impulse test, caloric test, fundus photography is needed to make an accurate diagnosis of BSVN.